Self-Care for Common Colds by Primary Care Patients: A European Multicenter Survey on the Prevalence and Patterns of Practices—The COCO Study - Thielmann, Anika (Evid Based Complement Alternat Med, 2016)
Background. Patients use self-care to relieve symptoms of common colds, yet little is known about the prevalence and patterns across Europe. Methods/Design. In a cross-sectional study 27 primary care practices from 14 countries distributed 120 questionnaires to consecutive patients (≥18 years, any reason for consultation). A 27-item questionnaire asked for patients' self-care for their last common cold. Results. 3,074 patients from 27 European sites participated. Their mean age was 46.7 years, and 62.5% were females. 99% of the participants used ≥1 self-care practice. In total, 527 different practices were reported; the age-standardized mean was 11.5 (±SD 6.0) per participant. The most frequent self-care categories were foodstuffs (95%), extras at home (81%), preparations for intestinal absorption (81%), and intranasal applications (53%). Patterns were similar across all sites, while the number of practices varied between and within countries. The most frequent single practices were water (43%), honey (42%), paracetamol (38%), oranges/orange juice (38%), and staying in bed (38%). Participants used 9 times more nonpharmaceutical items than pharmaceutical items. The majority (69%) combined self-care with and without proof of evidence, while ≤1% used only evidence-based items. Discussion. This first cross-national study on self-care for common colds showed a similar pattern across sites but quantitative differences.